2018
DOI: 10.1080/1828051x.2018.1425104
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary probiotic (Bacillus subtilis) supplementation on productive performance, immune response and egg quality characteristics in laying hens under high ambient temperature

Abstract: Effects of dietary probiotic (Bacillussubtilis) supplementation on productive performance, immune response and egg quality characteristics in laying hens under high ambient temperature,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
42
7
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 45 publications
8
42
7
9
Order By: Relevance
“…Various dietary strategies have been used to improve the poultry growth performance and feed efficiency, such as probiotics including Bacillus subtilis and Lactobacillus sp. Fathi et al 2018), prebiotics including fructooligosaccharides and galactooligosaccharides (Park et al 2017), forage products including alfalfa meal (Zheng et al 2019) and other natural products including green tea (Xia et al 2018). In this study, however, chickens fed diets containing chicory forage had a lower feed efficiency compared to those fed a basal diet.…”
Section: Discussioncontrasting
confidence: 53%
“…Various dietary strategies have been used to improve the poultry growth performance and feed efficiency, such as probiotics including Bacillus subtilis and Lactobacillus sp. Fathi et al 2018), prebiotics including fructooligosaccharides and galactooligosaccharides (Park et al 2017), forage products including alfalfa meal (Zheng et al 2019) and other natural products including green tea (Xia et al 2018). In this study, however, chickens fed diets containing chicory forage had a lower feed efficiency compared to those fed a basal diet.…”
Section: Discussioncontrasting
confidence: 53%
“…(Bidura dan Siti, 2017). Fathi et al (2018) melaporkan bahwa suplementasi probiotik tidak meningkatkan kinerja produksi telur, akan tetapi dapat meningkatkan kualitas kulit telur. Dilaporkan oleh Istiqomah et al (2018) bahwa Saccharomyces cerevisiae berpotensi untuk mengasimilasi kolesterol in vitro.…”
Section: Pendahuluanunclassified
“…Mengenai berat telur, ada peningkatan yang signifikan Karakteristik Kualitas Telur,dan Kolesterol Kuning Telur ..... pada ayam yang mendapat 0,20-0,30% probiotik Saccharomyces spp.Kb-13 dan telah menunjukkan resistensi yang lebih besar terhadap penyakit yang mempengaruhi sistem pencernaan (Prado et al, 2016). Sebaliknya, probiotik makanan tidak berpengaruh signifikan terhadap HU, indeks telur dan BJ telur (Fathi et al, 2018;dan Zurmiati et al, 2017). Hasil yang tidak konsisten dari suplemen probiotik mungkin karena perbedaan jumlah bakteri hidup yang sesuai, umur hewan, dan strain suplementasi (Chen et al, 2017).…”
Section: Hasil Dan Pembahasanunclassified
“…Most studies concerning modification of the functional properties of EWP are undertaken during food processing, and ,while the published studies on feed additives have been related to the effects of additives on egg quality (egg weight, eggshell strength, yolk color, etc. ), little is known about the influence of feed additives on the functional properties of EWP . Supplementation with curcumin in the diet of laying hens has been reported to increase antioxidant levels in eggs, reduce lipid peroxidation in fresh and stored eggs, and improve egg quality .…”
Section: Introductionmentioning
confidence: 99%
“…), little is known about the influence of feed additives on the functional properties of EWP. 7,8 Supplementation with curcumin in the diet of laying hens has been reported to increase antioxidant levels in eggs, reduce lipid peroxidation in fresh and stored eggs, and improve egg quality. 9 Fathi et al 8 showed that a diet supplemented with probiotics has a beneficial effects on eggshell quality and resistance to breaking.…”
Section: Introductionmentioning
confidence: 99%